Strength training for young athletes - Kraemer, William J., 1953- 4 0 16; 1951- Fleck, Steven J.; 5 (Champaign, IL : Human Kinetics, 2005)
Presents a practical guide for strength development for young athletes ages seven to eighteen and provides instruction on a number of exercises, proper training, and creating individualized programs.
Includes bibliographical references (p. 280-283) and index.
Keywords: 2 -- 0; 6; Exercise.;Isometric exercise; 20; 2